2003
DOI: 10.1108/00220410310698734
|View full text |Cite
|
Sign up to set email alerts
|

Citation counts and the Research Assessment Exercise V

Abstract: A citation study of the 692 staff that makes up unit of assessment 58 (archaeology) IntroductionIn this paper, we describe research on the correlation between citation counts and an of®cial 2001 assessment of research excellence in UK university archaeology departments. To assess the research performance of UK universities, the UK Higher Education Funding Councils carry out a periodic Research Assessment Exercise (RAE). The RAE is concerned with making a qualitative judgement of the research output of those u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
2
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 23 publications
3
56
2
1
Order By: Relevance
“…For instance, Nederhof et al (1989) have made partial measures in the case of a sample of departments at Dutch universities. Small and Crane (1979) have examined the use of books in the field of sociology while Norris and Oppenheim (2003) examined the production of archeologists and Andersen (2000) inquired about the media used in the social sciences in general.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Nederhof et al (1989) have made partial measures in the case of a sample of departments at Dutch universities. Small and Crane (1979) have examined the use of books in the field of sociology while Norris and Oppenheim (2003) examined the production of archeologists and Andersen (2000) inquired about the media used in the social sciences in general.…”
Section: Resultsmentioning
confidence: 99%
“…Studying six economics research groups from 1980 to 1988, Nederhof and van Raan (1993) found that 37% of the groups' combined production was composed of journal articles. Within the framework of the Research Assessment Exercise (RAE) in the United Kingdom, Norris and Oppenheim (2003) evaluated the performance of 682 archaeologists. The authors found that 54% of the archaeologists' publications were monographs and 40% articles.…”
Section: Non-journal Publications In the Social Sciences And Humanitiesmentioning
confidence: 99%
“…Norris and Oppenheim (2003). Franceschet and Costantini (2011) look at the relationship between various citation based research quality measures and outcomes from the first Italian research assessment exercise.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, there is an increasing body of evidence to support the view that bibliometric approaches can yield results closely mirroring the judgments of subject experts. Specifically, significant correlations have been observed between expert judgments and bibliometric data in comparisons carried out in Italy (Abramo et al, 2009;Reale et al, 2007), the Netherlands (Rinia et al, 1998;van Raan, 2006) and the UK (Norris and Oppenheim, 2003;Oppenheim, 1997;Seng and Willett, 1995). That said, bibliometrics has its own limitations, and these would have to be borne in mind if a decision was taken at some point in the future to base research evaluation solely on bibliometric data, without recourse to expert judgments.…”
Section: Introductionmentioning
confidence: 99%